Pengaruh Bauran Pemasaran Terhadap Keputusan Pembelian Sepeda Motor Merk Honda di PT. Nusantara Surya Sakti Pontianak - Sinhan 01; Japari A (JURNAL MANAJEMEN MOTIVASI, 2015)
Purpose of this study was to determine the effect of the marketing mix on purchase decisions of Honda motorcycles in PT Nusantara Surya Sakti Pontianak. The study is a descriptive study, using data collected through observation, interviews, questionnaires, and corporate documents. The population of consumers who purchased a motorcycle brands Honda PT. NSS Pontianak and the sample is determined as much as 97 respondents. Terms samples are age (20-56) old, Buying motorcycle brands Honda for its own purposes, able to read and write well, Domiciled in Pontianak City and surrounding areas. The analytical tool used is a simple regression. The results showed that the constant value obtained was 0.079, meaning that if the elements of the marketing mix is 0 (zero), then the consumer purchase decisions of Honda motorcycles brands in PT Nusantara Surya Sakti would be worth 0.079. Simple regression coefficient value of the marketing mix variables obtained at 0.964, meaning that if the marketing mix is increased by one unit, then the purchasing decisions of consumers on the purchase of Honda's motorcycle brands in PT. Nusantara Surya Sakti Pontianak will increase by 0.964 units.